The generalized Stackelberg equilibrium of the all-pay auction with complete information - Kai A. Konrad; Wolfgang Leininger (Universität Dortmund, Wirtschafts- und Sozialwissenschaftliche Fakultät, 2005)
We characterize the equilibrium of the all-pay auction with general convex cost of effort and sequential effort choices. We consider a set of n players who are arbitrarily partitioned into a group of players who choose their efforts 'early' and a group of players who choose 'late'. Only the player with the lowest cost of effort has a positive payoff in any equilibrium. This payoff depends on his own timing vis-a-vis the timing of others. We also show that the choice of timing can be endogenized, in which case the strongest player typically chooses 'late', whereas all other players are indifferent with respect to their choice of timing. In the most prominent equilibrium the player with the lowest cost of effort wins the auction at zero aggregate cost.
Keywords: D72; D74; 330; Sequential all-pay auction; complete information; generalized cost; generalized Stackelberg game